THE EFFECT OF LEADERSHIP STYLE AND COMPENSATION ON ORGANIZATIONAL COMMITMENT OF BABINSA IN JAKARTA - Dicky Hida Syahchari; Lifany Husnul Kurnia (The Republic of Indonesia Defense University, 2018)
This study investigates the conceptualization of the leadership style and compensation within organizational commitment of Babinsa in Jakarta as well as examining the leadership style and compensation on organizational commitment by previous researchers. This study use qualitative method by reviewing and integrates previous studies to point to the significance of the leadership style and compensation towards organizational commitment of Babinsa specifically in Jakarta. This study proposes a research framework to investigate the relationship of leadership style and compensation on organizational commitment of Babinsa in Jakarta. The study is particularly useful for practitioners by identifying advantages of suitable organizational commitment of Babinsa in Jakarta.